Acute incarceration prolapsed solitary rectal ulcer: a rare case of anorectal emergency - Norfaidhi, Akram M N; Sainal, Mohd. Yusof; Elagili, Faisal; Md Nor, Azmi (2021)
OBJECTIVE We aim to report a case of acute incarceration prolapsed giant solitary rectal ulcer that was treated successfully by transanal excision. CASE REPORT A 17-year-old male presented to emergency department with acute an incarcerated mass protruding from the anal canal 3 hours prior. Patient was diagnosed with a solitary rectal ulcer syndrome for one year-old and started receiving medical treatment with signs of partial recovery. On clinical examination, vital signs within normal limits. His abdomen was not tender and had no signs of peritoneal irritation. Rectal examination revealed 15cm x 10cm incarcerated prolapsed mass, looked like cauliflower, because of the failure of external manual reduction we decided to bring the patient to the operating room. The mass was removed by transanal excision under spinal anesthesia and the histopathologic result is consistent with solitary rectal ulcer. CONCLUSION Our case is a rare presentation of SRUS, although less common than other causes of prolapsed anal mass, it should be considered as part of the differential diagnosis.